The Role Of E-training In Developing The Professional Development Of Faculty Members Imam Muhammad Bin Saud Islamic University - Yousef Saud Z. Alharbi; Ahmed bin Yussuf; Syed Mohammad Hilmi Bin Syed Abdul Rahman (OCERINT International, 2024)
Non-Indexed Publication